Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Berpikir Kreatif Siswa Materi Bangun Ruang Kelas V SDN Pademawu Timur 2 - Alamsyah, Ummi Abidah Zuhlah; Wulandari, Rika (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research aims to determine the significant influence of the application of the project based learning model on the creative thinking abilities of fifth grade students at SDN Pademawu Timur 2. This research is quantitative research with the type of experimental research, the research design used is a quasi experimental design, and the design form is used is a nonequivalent control group design. The sample used was 32 students at SDN Pademawu Timur 2 consisting of class V-A and class V-B. This research uses an experimental class and a control class. Data was collected using observation, interviews, and creative thinking ability tests. Trials on creative thinking ability test questions use validity tests, reliability tests, and the level of difficulty of the questions. The data analysis used is a prerequisite test using the normality test and homogeneity test, and hypothesis testing using the independent sample t test. Based on the results of data analysis in hypothesis testing using the independent sample t test, the pre-test value was 0.0529, so Sig. (2-tailed) > 0.05, which means there is no significant difference between the control and experimental classes before treatment is given. Meanwhile, after being given treatment, the results of the independent sample t test hypothesis test obtained a post test value of 0.002, so Sig. (2-tailed) < 0.05, which means there is a significant difference. So it can be concluded that there is an influence on the application of the project based learning model on the creative thinking abilities of class V students at SDN Pademawu Timur 2.